2021
DOI: 10.3390/jof7110942
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Profiling of Metarhizium anisopliae—Responsive microRNAs Involved in Modulation of Plutella xylostella Immunity and Development

Abstract: Metarhizium anisopliae, a ubiquitous pathogenic fungus, regulates a wide array of the insect pest population. The fungus has been employed to control Plutella xylostella, an insecticide-resistant destructive lepidopteran pest, which causes substantial economic losses in crops worldwide. Integration of modern gene-silencing technologies in pest control strategies has become more crucial to counter pesticide-resistant insects. MicroRNAs (miRNA) play essential roles in the various biological process via post-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…The potential lncRNAs identified in our study as miRNA precursors are presented in Tables S13 and S14 . We filtered these miRNAs through our previous studies to identify their potential immunity and development-related target genes [ 54 , 55 ] and identified several important genes, including trypsin , serpin B1 , catalase , cholinesterase , chymotrypsin, and cytochrome p450 . A schematic diagram of the lncRNA-miRNA-mRNA complex is presented in Figure 3 , particularly focusing on immune-related genes.…”
Section: Resultsmentioning
confidence: 99%
“…The potential lncRNAs identified in our study as miRNA precursors are presented in Tables S13 and S14 . We filtered these miRNAs through our previous studies to identify their potential immunity and development-related target genes [ 54 , 55 ] and identified several important genes, including trypsin , serpin B1 , catalase , cholinesterase , chymotrypsin, and cytochrome p450 . A schematic diagram of the lncRNA-miRNA-mRNA complex is presented in Figure 3 , particularly focusing on immune-related genes.…”
Section: Resultsmentioning
confidence: 99%
“…MiRNAs are considered to be vital players in insect host− pathogen interactions. 48 Insects, as well as viruses, exploit miRNAs for their specific benefits. Studies conducted on several insect species have shown the response of host miRNAs to pathogen stress and revealed the differential expression of a vast number of miRNAs.…”
Section: ■ Discussionmentioning
confidence: 99%
“…To systematically identify the AcMNPV-induced DEGs in the S. f rugiperda larval midgut, whole-transcriptome sequencing was performed at different time points (6,48, and 72 h). Differential expression analysis was carried out to determine variations in gene expressions followed by AcMNPV infection.…”
Section: Expression Patterns Of Immune Genes In S F Rugiperda Midgut ...mentioning
confidence: 99%
“…A total reaction mixture of 25 μL was used, while rp49 was used as an internal control to normalize the expression of ecdysone signaling-related genes by the 2 −ΔΔ CT method. The conditions used were: 95 °C for 2 min, 40 cycles each of 95 °C for 5 s, 60 °C for 10 s, and melting curve from 65–95 °C [ 25 , 26 ]. Further, 3 biological replicates were used and each biological replicate was repeated 3 times with 20 ovaries per replicate.…”
Section: Methodsmentioning
confidence: 99%